THU0054 NKTR-358, A NOVEL IL-2 CONJUGATE, STIMULATES HIGH LEVELS OF REGULATORY T CELLS IN PATIENTS WITH SYSTEMIC LUPUS ERYTHEMATOSUS. (2nd June 2020) - Siddhanti, S.; Fanton, C.; Dixit, N.; Lu, L.; Chindalore, V.; Levin, R.; Diab, I.; Furie, R.; Zalevsky, J.; Kotzin, B.
Abstract : Background: Impaired IL-2 production and dysfunction of regulatory T cells (Tregs) have been identified as key immunological defects leading to the breakdown of immune self-tolerance in SLE. Low-dose IL-2 can expand Tregs, but the effect is limited by a narrow therapeutic window for Treg selectivity. Furthermore, the short half-life of IL-2 necessitates frequent administration. NKTR-358 is a polyethylene glycol (PEG) conjugate of recombinant human IL-2 (aldesleukin sequence) and is differentiated from native IL-2 by its altered binding to the IL-2 receptor and prolonged biological activity. NKTR-358 resulted in marked and selective stimulation of Tregs when administered as a single SC injection to healthy volunteers. Objectives: This multiple ascending dose study assessed the safety, tolerability, pharmacokinetics (PK), and immune effects of NKTR-358 in patients with SLE after repeated administration of SC doses. The time course and extent of changes in numbers and percentages of Tregs, conventional CD4+ and CD8+ T cells, NK cells, and cytokine levels in peripheral blood were investigated. Methods: In this double-blind, multiple ascending dose study, patients with mild to moderate SLE received 3 SC doses q2w in 4 cohorts ranging from 3.0 to 24.0 µg/kg (9 active:3 placebo per cohort); patients were followed for a total of 79 days. Results: There were no dose-limiting toxicities, deaths, or clinically significant abnormalities in either vital signs or electrocardiograms. Adverse events attributed to NKTR-358 were primarily limited to mild (grade 1) injection site reactions. At the highest dose, one subject had transient and mild (grade 1) symptoms of a flu-like syndrome after administration, without associated elevated cytokine levels, and another subject had dosing stopped due to elevated eosinophil levels. No other individual at any dose level had systemic signs or symptoms known to be associated with IL-2 therapy. No anti-drug antibodies were detected. NKTR-358 demonstrated dose-proportional PK with repeated dosing; plasma levels peaked 3-6 days post-dose and declined with a terminal half-life of ~10-13 days. The primary and consistent effect of NKTR-358 was seen on Tregs. In the four dose cohorts, dose-dependent and sustained increases in absolute numbers and percentages of circulating CD4+FoxP3+CD25 bright Tregs were observed. Treg levels remained elevated throughout the dosing period, peaking at Day 10 after the first administration of NKTR-358 and returning to baseline ~ 20-30 days following last administration. At 24.0 µg/kg, the mean peak increase in numbers of CD25 bright Tregs was 11-fold above baseline. In addition, there was an increase in Treg activation markers at doses ≥12.0 µg/kg. In contrast to effects on Tregs, no changes in percentages or numbers of conventional CD4+ or CD8+ T cells were observed at any dose tested. At the highest dose, there were low-level increases in the percentages and numbers of NK cells. Overall, NKTR-358 selectively induced Tregs, evidenced by a 12-fold increase in the mean peak Treg:CD8 ratio over baseline in the 24.0 µg/kg group. Conclusion: NKTR-358, an IL-2 conjugate Treg stimulator, was well tolerated when repeatedly administered (q2w) at doses up to 24 µg/kg. Its administration led to marked, selective, prolonged, and dose-dependent increases in circulating CD25 bright Tregs. This clinical study in SLE patients extends the previous results in healthy volunteers and provides strong support for continued testing of NKTR-358 as a new therapeutic in SLE and other inflammatory diseases. Disclosure of Interests: Suresh Siddhanti Shareholder of: Nektar Therapeutics, Employee of: Nektar Therapeutics, Christie Fanton Shareholder of: Nektar Therapeutics, Employee of: Nektar Therapeutics, Neha Dixit Shareholder of: Nektar Therapeutics, Employee of: Nektar Therapeutics, Lin Lu Shareholder of: Nektar Therapeutics, Employee of: Nektar Therapeutics, Vishala Chindalore Grant/research support from: Nektar Therapeutics for conducted studies, Speakers bureau: > 5 years ago, Robert Levin Grant/research support from: Payments for clinical research for industry-sponsored trials, Consultant of: Gilead, Exagen, Myriad Rheumatology, Speakers bureau: Sanofi/Genzyme, Regeneron, Bristol-Myers Squibb, AbbVie, Isam Diab: None declared, Richard Furie Grant/research support from: Nektar Therapeutics to Northwell Rheumatology to conduct this study, Consultant of: Nektar Therapeutics, Jonathan Zalevsky Shareholder of: Nektar Therapeutics, Employee of: Nektar Therapeutics, Brian Kotzin Shareholder of: Nektar Therapeutics, Employee of: Nektar Therapeutics